2022
DOI: 10.37934/arfmts.100.1.7788
|View full text |Cite
|
Sign up to set email alerts
|

Banana Peels Pectin Templated Silica Ultrafiltration Membrane in Disk Plate Configuration Applied for Wetland Water Treatment

Abstract: South Kalimantan has natural surface water such as wetland water which easily found to prevent water scarcity. Two types of wetland water provided in tropical area i.e. (1) peat water which located in land area; and (2) wetland saline water that area is near to coastal zone. Both are unsuitable for consumption and required to be treated. Ultrafiltration (UF) is one of methods that can be applied for treating natural wetland water using silica membrane. However, it needs improved by carbon due to lacking its lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The development of these membranes has progressed significantly in recent years, resulting in superior performance and increased application [11,12]. Numerous studies have demonstrated that the development of hollow fiber membranes typically centres on modifying or creating new membranes to obtain desirable properties, including porosity, permeability, rejection, hydrophilicity, thermal stability, and mechanical stability [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The development of these membranes has progressed significantly in recent years, resulting in superior performance and increased application [11,12]. Numerous studies have demonstrated that the development of hollow fiber membranes typically centres on modifying or creating new membranes to obtain desirable properties, including porosity, permeability, rejection, hydrophilicity, thermal stability, and mechanical stability [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[5,6]. Silica is an interesting material to apply for inorganic membrane fabrication, due to it provides excellent molecular sieving, formidable, withstanding to extreme temperatures and chemicals, and less fouling than polymer-based membranes [7][8][9][10][11][12][13]. However, silica membranes also have the main disadvantage of having low stability when in contact with water [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Today, the human population is increasing along with its demand which affects industrial and agricultural sector [1][2][3][4][5][6][7][8][9]. Besides that, especially Indonesia as agraris country has a large area of land even though it's an archipelago form [10][11][12][13][14].Weed growth in agricultural activities is often an obstacle to the growth and production of cultivated plants.…”
Section: Introductionmentioning
confidence: 99%